Jemaah Ahmadiyah Indonesia (JAI) di Jakarta: Eksistensi Pasca Surat Keputusan Bersama Tentang Ahmadiyah Tahun 2008-2011 - Adea Tiara (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This writing was motivated by the issuance of a Joint Decree of the Three Ministers (SKB) issued by the Minister of Religion, the Attorney General's Office, the Minister of Home Affairs of the Republic of Indonesia regarding the warning not to spread interpretations regarding the recognition of the existence of a prophet after the Prophet Muhammad for the Ahmadiyah movement which has developed in Indonesia since before independence era. This writing uses a multidimensional approach and historical method by paying attention to the stages which include Heuristics, Verification, Interpretation, and Historiography. The purpose of this paper is to find out the existence of the existence of the Indonesian Ahmadiyya Community (JAI) in Jakarta after the issuance of the Joint Decree of the Three Ministers (SKB) in 2008-2011 and to find out how the Indonesian Ahmadiyya Community (JAI) organization continues to exist in the community. The results of the study show that the existence of the Indonesian Ahmadiyya Community (JAI) still exists in the community. Although at the beginning of the issuance of the decree, the Ahmadiyah in Jakarta experienced acts of discrimination in the form of burning and sealing mosques. Nevertheless, the Ahmadiyya Community in Jakarta was able to survive by pursuing it through internal and external strategies. Penulisan ini dilatarbelakangi oleh diterbitkannya Surat Keputusan Bersama (SKB) yang dikeluarkan oleh Menteri Agama, Kejaksaan Agung, Menteri Dalam Negeri Republik Indonesia tentang peringatan untuk tidak menyebarkan penafsiran mengenai pengakuan keberadaan nabi setelah Nabi Muhammad bagi gerakan Ahmadiyah yang telah berkembang di Indonesia sejak sebelum era kemerdekaan. Penulisan ini menggunakan pendekatan multidimensional dan metode sejarah dengan memperhatikan tahapan-tahapan yang meliputi Heuristik, Verifikasi, Interpretasi, dan Historiografi. Tujuan dari penulisan ini untuk mengetahui keberadaan Jemaah Ahmadiyah Indonesia (JAI) di Jakarta pasca dikeluarkannya Surat Keputusan Bersama (SKB) tahun 2008-2011, serta untuk mengetahui bagaimana organisasi Jemaah Ahmadiyah Indonesia (JAI) tetap eksis di masyarakat. Hasil penelitian menunjukan eksistensi Jemaah Ahmadiyah Indonesia (JAI) masih tetap ada di masyarakat. Walaupun pada awal dikeluarkan surat keputusan tersebut Ahmadiyah di Jakarta mengalami tindakan diskriminasi berupa pembakaran dan penyegelan masjid. Meskipun demikian, Jemaah Ahmadiyah di Jakarta mampu bertahan dengan mengupayakan melalui strategi internal maupun eksternal.